2014
DOI: 10.1016/j.neuron.2014.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Axon-Derived Signals Couple Target Survival and Layer Specificity in the Drosophila Visual System

Abstract: SUMMARY Neural circuit formation relies on interactions between axons and cells within the target field. While it is well established that target-derived signals act on axons to regulate circuit assembly, the extent to which axon-derived signals control circuit formation is not known. In the Drosophila visual system, anterograde signals numerically match R1–R6 photoreceptors with their targets by controlling target proliferation and neuronal differentiation. Here we demonstrate that additional axon-derived sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 82 publications
(121 reference statements)
2
51
0
Order By: Relevance
“…First, we ablated L3s through cell-type specific RNAi-mediated knock-down of a neurotrophic receptor. This experiment was originally published by our group where we showed that removal of all L3s led to a loss of Net from the M3 layer (Pecot et al, 2014). To compare the development of R8s with and without a home-column L3 in the same brain, we reduced the efficiency of the knock-down to achieve a partial ablation of the L3 array (~80% loss with ~20% surviving through eclosion).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…First, we ablated L3s through cell-type specific RNAi-mediated knock-down of a neurotrophic receptor. This experiment was originally published by our group where we showed that removal of all L3s led to a loss of Net from the M3 layer (Pecot et al, 2014). To compare the development of R8s with and without a home-column L3 in the same brain, we reduced the efficiency of the knock-down to achieve a partial ablation of the L3 array (~80% loss with ~20% surviving through eclosion).…”
Section: Resultsmentioning
confidence: 97%
“…For a more refined approach to studying the role of Net in R8 targeting, we pursued two strategies involving genetic manipulation of the L3 lamina monopolar neuron, the principal source of Net in the target layer (Pecot et al, 2014; Timofeev et al, 2012). First, we ablated L3s through cell-type specific RNAi-mediated knock-down of a neurotrophic receptor.…”
Section: Resultsmentioning
confidence: 99%
“…The simplest interpretation of the matching of Dprs and DIPs in synaptic partners is that these proteins regulate synaptic specificity. It would not be surprising, however, if these proteins play different roles such as contributing to layer-specific targeting, as with N-cadherin (Lee et al, 2001) or netrin (Timofeev et al, 2012), or cell-type-specific trophic support as we described previously for Jeb/Alk signaling (Pecot et al, 2014). Detailed phenotypic analyses of null mutants lacking Dprs and DIPs, and given the redundancy within these families, perhaps genetic analysis of animals lacking combinations of them, will be required to ascertain the precise functions of this family of ligand/receptor pairs in circuit assembly.…”
Section: Discussionmentioning
confidence: 98%
“…Other OL neurons are also dependent on trophic factors for survival. R cell growth cones secrete the Jelly Belly (Jeb) ligand, which binds to its receptor Alk on L3 neurons, and L3s die in the absence of Jeb or Alk (Pecot et al, 2014). The functions of DIP-γ in mediating normal development of yR7-Dm8 connectivity, as assayed by displacement of the active zone marker in yR7s, may be distinct from its roles in Dm8 survival, because about half of the overshoots in DIP-γ mutants appear to grow through a Dm8 arbor labeled by the DIP-γ reporter (Figure 7D).…”
Section: Discussionmentioning
confidence: 99%